TINGKAT PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP KONSEP DASAR AKUNTANSI DI PERGURUAN TINGGI NEGERI DI KOTA MALANG - Mawardi, M. Cholid (Fakultas Ekonomi, UIN Maliki Malang, 2012)
The purpose of this study was to measure the gap of understanding that comes from the vocational school students majoring in accounting, high school social studies and Madrasah Aliyah Department of General of the basic concepts of accounting. The basic concept of accounting is used as a variable in this research that the assets, liabilities and capital. Techniques of data collection in this research using questionnaires. Population and sample in this study were 100 students majoring in accounting at the State Universities in Malang City listed as an active student for the academic year 2010/2011 and has completed introductory accounting courses I and II. This study uses a different test Kruskal Wallis to measure the gap of understanding that comes from the vocational school students majoring in accounting, high school social studies majors and Madrasah Aliyah General of the basic concepts of accounting. The results show that, of the three variables are used as the measurement of differences in levels of student understanding of basic concepts of accounting are assets, liabilities, capital and otherwise there is no students' understanding of basic concepts of accounting. From the mean rank of three variables it is seen that students from Madrasah Aliyah better understand the basic concepts of accounting compared to students from SMK Accounting Department and high school social studies majors.